The late IIIRD millennium collective grave ‒ investigating the ritual funerary context in a brickwork silo in the ancient city of Šuruppag (Fāra) - Paszke, Marcin Zygmunt (Acta Archaeologica Lodziensia, 2024)
The present research elaborates on a brickwork silo discovered by Schmidt’s excavation team at Fāra in southern Mesopotamia. This structure held eight skeletons, mostly deposited in a haphazard and careless manner. It was thought that the skeleton assemblage had not been granted any grave goods. The stratigraphical and contextual analysis of the silo content, roughly dated to the Ur III period, argues for a different interpretation. It seems that the bodies deposited inside the silo had been equipped with exceptional terracotta objects used to secure the place of the collective burial against ghosts who could harm the living people due to an improper interment of the bodies. The silo at Fāra offers a unique opportunity to understand the function of terracotta figurines and of models used in Mesopotamian magic.